PENERAPAN METODE FULL COSTING DALAM MENENTUKAN HARGA POKOK PRODUKSI MINYAK KAYU PUTIH PADA UD BIAM DI KOTA AMBON - CHRESTIANA APONN0 (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The purpose of this study was to determine the cost of goods produced by eucalyptus oil. This research uses the full costing method to determine the cost of goods produced. The full costing method is a method in determining the cost of goods of a product by taking into account all production costs such as raw material costs, direct labor, and factory overhead costs that are variable or fixed. The results showed that in July 2022 eucalyptus oil was prosuctioned as many as 50 bottles. The costs incurred are: raw material costs of Rp. 1,500,000, direct labor costs of Rp. 4,000,000, factory overhead costs of Rp. 779,000. The cost of goods produced of eucalyptus oil per bottle is Rp. 125,580.